RNAi Transfection Optimized in Primary Naïve B Cells for the Targeted Analysis of Human Plasma Cell Differentiation - Shih, Tiffany; De, Saurav; Barnes, Betsy J. (Frontiers in Immunology, 2019)
Upon antigen recognition, naïve B cells undergo rapid proliferation followed by differentiation to specialized antibody secreting cells (ASCs), called plasma cells. Increased circulating plasma cells are reported in patients with B cell-associated malignancies, chronic graft-vs.-host disease, and autoimmune disorders. Our aim was to optimize an RNAi-based method that efficiently and reproducibly knocks-down genes of interest in human primary peripheral B cells for the targeted analysis of ASC differentiation. The unique contributions of transcriptional diversity in species-specific regulatory networks and the mechanisms of gene function need to be approached directly in human B cells with tools to hone our basic inferences from animal models to human biology. To date, methods for gene knockdown in human primary B cells, which tend to be more refractory to transfection than immortalized B cell lines, have been limited by losses in cell viability and ineffective penetrance. Our single-step siRNA nucleofector-based approach for human primary naïve B cells demonstrates reproducible knockdown efficiency ( 40–60%). We focused on genes already known to play key roles in murine ASC differentiation, such as interferon regulatory factor 4 (IRF4) and AID. This study reports a validated non-viral method of siRNA delivery into human primary B cells that can be applied to study gene regulatory networks that control human ASC differentiation.